Positive‐strand RNA viruses—a Keystone Symposia report. Issue 1 (25th January 2023) - Cable, Jennifer; Denison, Mark R.; Kielian, Margaret; Jackson, William T.; Bartenschlager, Ralf; Ahola, Tero; Mukhopadhyay, Suchetana; Fremont, Daved H.; Kuhn, Richard J.; Shannon, Ashleigh; Frazier, Meredith N.; Yuen, Kwok‐Yung; et al.
Abstract: Positive‐strand RNA viruses have been the cause of several recent outbreaks and epidemics, including the Zika virus epidemic in 2015, the SARS outbreak in 2003, and the ongoing SARS‐CoV‐2 pandemic. On June 18–22, 2022, researchers focusing on positive‐strand RNA viruses met for the Keystone Symposium "Positive‐Strand RNA Viruses" to share the latest research in molecular and cell biology, virology, immunology, vaccinology, and antiviral drug development. This report presents concise summaries of the scientific discussions at the symposium. Abstract : Positive‐strand RNA viruses have been the cause of several recent outbreaks and epidemics, including the Zika virus epidemic in 2015, the SARS outbreak in 2003, and the ongoing SARS‐CoV‐2 pandemic. On June 18–22, 2022, researchers focusing on positive‐strand RNA viruses met for the Keystone Symposium "Positive‐Strand RNA Viruses" to share the latest research in molecular and cell biology, virology, immunology, vaccinology, and antiviral drug development.